Equine Science 2020
DOI: 10.5772/intechopen.91290
|View full text |Cite
|
Sign up to set email alerts
|

Current Strategies for Prevention and Treatment of Equine Postoperative Ileus: A Multimodal Approach

Abstract: Equine paralytic (postoperative) ileus generally refers to an acute condition of impaired gastrointestinal motility. Paralytic ileus is most frequently seen following abdominal surgery on the small intestine in horses. Three main mechanisms are involved separately or simultaneously in its causation, namely neurogenicendocrinic, inflammatory-endotoxic and pharmacological mechanisms. Regardless of the cause, equine paralytic ileus can be fatal, if not properly diagnosed and treated. Over the past 22 years (1997-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 117 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…Based on our examination, the prognosis of surgical cure of enteroliths and other forms of small colon constipation in horses is good (compared to other small intestine pathologies) in case of rapid diagnosis and timely treatment of such horses (Kovač et al, 2015;Kovač et al, 2019). Based on our long-term examination, postoperative (paralytic) ileus in the small colon pathology practically does not occur in horses, compared to small intestine pathologies (Kovač et al, 2020). However, if intestinal necrosis has occurred due to the prolonged presence of enteroliths, small colon resection is required (in addition to removal of enteroliths).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Based on our examination, the prognosis of surgical cure of enteroliths and other forms of small colon constipation in horses is good (compared to other small intestine pathologies) in case of rapid diagnosis and timely treatment of such horses (Kovač et al, 2015;Kovač et al, 2019). Based on our long-term examination, postoperative (paralytic) ileus in the small colon pathology practically does not occur in horses, compared to small intestine pathologies (Kovač et al, 2020). However, if intestinal necrosis has occurred due to the prolonged presence of enteroliths, small colon resection is required (in addition to removal of enteroliths).…”
Section: Discussionmentioning
confidence: 93%
“…All postoperative horses underwent standard postoperative therapy (infusion therapy, antibiotics, nonsteroidal anti-inflammatory drugs, and prokinetics) (Kovač et al, 2020). During postoperative hospitalization, 3 horses were euthanized or died due to septic peritonitis, endotoxemia, and adhesive ileus.…”
Section: Resultsmentioning
confidence: 99%
“…POI may result from intestinal ischaemia or physical trauma (distension and handling) during surgery leading to the activation of intestinal macrophages, which release cytokines and nitric oxide, further inhibiting intestinal motility (Doherty, 2009). It is also likely that, as NSAIDs reduce pain and inflammation, which is in turn associated with impaired GI motility due to sympathetic stimulation (Kovac et al, 2020), this mechanism is another explanation as to why NSAIDs have been found to help prevent POI. In a study investigating the prevention of POI, flunixin was a commonly prescribed drug (Lefebvre et al, 2016); however, there is no evidence that flunixin is superior to meloxicam when it comes to the POI prophylaxis in surgical colic patients (Naylor et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous equine pathologies that are directly or indirectly associated with stress factors. According to our clinical experience, due to stress exposure, the most commonly noticed diseases in horses are-gastric ulcers, proximal enteritis, acute colitis, and pleuropneumonia [177][178][179]. It is important to note that for the occurrence of these diseases along with stress, other pathogenomonic factors have also had a significant impact.…”
Section: Pathophysiology Of Equine Stressmentioning
confidence: 97%
“…For example, for the occurrence of paralytic ileus or colitis, a high concentration of endotoxins in the blood also plays a very important role [177,178]. Noxious gases (e.g., NH, NO, and CO) in the transport environment may be partially responsible for transport-related equine pleuropneumonia [179]. It is known that equine transport causes strong psychological stress reactions as it often combines the effects of neophobia, claustrophobia, social separation, and balancing.…”
Section: Pathophysiology Of Equine Stressmentioning
confidence: 99%